Pengaruh Tunjangan Kinerja, Komunikasi, dan Motivasi Kerja Terhadap Kinerja Pegawai pada Kantor Imigrasi Kelas I TPI Polonia Medan - Boyke W. H. Lumban Tobing; Siti Normi; Elperida J. Sinurat (Universitas Methodist Indonesia, 2026)
This study aims to determine and analyze the influence of performance allowances, communication, and work motivation on employee performance at the Polonia Class 1 Immigration Office. This study employed a quantitative approach, which is structured and quantifies data for generalizability. The sample size was 72 respondents. Based on the results of the t-test, it can be concluded that performance allowances influence employee performance, communication influences employee performance, and work motivation influences employee performance. Based on the results of the F-test, it can be concluded that simultaneously, performance allowances, communication, and work motivation have a significant effect on employee performance. The coefficient of determination analysis yielded an Adjusted R Square of 0.683, meaning that 68.3% of employee performance can be explained by performance allowances, communication, and work motivation. The remaining 31.7% (100% - 68.3%) can be explained by other variables not examined in this study.